Immobilized Au nanoparticles on chitosan-biguanidine modified Fe3O4 nanoparticles and investigation of its anti-human lung cancer activity - Yang Xue; Bikash Karmakar; Jianlin Ke; Hala A. Ibrahium; Nasser S. Awwad; Attalla F. El-kott (Journal of Saudi Chemical Society, 2022)
In current nanoscience bioengineered magnetic nanoparticles (NPs) have come into prominence with considerable impact. These advanced functional materials find outstanding applications in chemical science in catalysis, environmental issues, sensing etc, as well as in biology as drug delivery agent, chemical therapeutics and others. We have been prompted to architect and synthesize a novel Au NP adorned over chitosan-biguanidine polyplex modified core–shell type magnetic nanocomposite (Fe3O4/CS-biguanidine/Au NPs). The bioshells facilitate to protect the core ferrite NPs as well as provides stability to the synthesized Au NPs by capping. The material was characterized using different analytical techniques like Fourier Transformed Infra-Red spectroscopy (FT-IR), Inductively Coupled Plasma-Optical Emission Microscopy (ICP-OES), Field Emission Scanning Electron Microscopy (FE-SEM), Energy Dispersive X-ray spectroscopy (EDX), Transmission Electron Microscopy (TEM), Vibrating Sample Magnetometer (VSM) and X-ray Diffraction (XRD) studies. We explored the biological application of the nanocomposite in determining cytotoxicity of three adenocarcinoma cell lines (PC-14, LC-2/ad, HLC-1) through the MTT assay. The material showed very good activity by exhibiting very low % cell viability over the cell lines dose-dependently. The IC50 of Fe3O4/CS-biguanidine/Au NPs were observed 503, 398 and 475 µg/mL respectively against the three cell lines. The best output was observed at a concentration of 1000 µg/mL of catalyst in terms of cytotoxicity and inhibition of lung cancer growth. The anti-cancer potential was found in close relation to their antioxidant potential.